Effect of a nondominant perforator on multiterritory perforator flap survival in rats. Issue 5 (21st May 2019) - Wang, Long; Wu, Hongqiang; Yan, Hede; Dong, Xiaoming; He, Zhiling; Ding, Jian; Gao, Weiyang
Abstract: Background: During flap surgery, the dominant perforator is usually selected as the pedicle. This study investigated the effect of a nondominant perforator on multiterritory perforator flap survival. Methods: The deep circumflex iliac artery perforator flap (DCIA flap) and intercostal artery perforator flap (ICA flap) were performed ( n = 12). Only the pedicle was different between the two flaps. The DCIA flap was based on the right and peripheral DCIA with three dynamic and two potential perforasomes. The ICA flap was based on the right and central ICA with five dynamic perforasomes. All adjacent perforators were ligated except the pedicle. On postoperative day 7, flap viability, angiography findings, and perfusion were compared. Results: Even though the diameter of DCIA (mm) was larger than that of ICA (0.49 ± 0.03 vs. 0.4 ± 0.04; p < .05), the ICA flap survival rate (%) was higher than that of DCIA flap (99.5 ± 0.7 vs. 83.8 ± 3.9; p < .001). Based on a dominant perforator, a necrotic area was observed in the potential perforasomes of the DCIA flap. The choke vessels between the anatomical and dynamic perforasomes dilated postoperatively in the two flaps, whereas the others did not. The perfusion (PU) differences between the DCIA and ICA flaps in the dynamic perforasomes were nonsignificant (average, 342.4 ± 9.1 vs. 347.3 ± 7.3; p > .05). Conclusion: Increasing the number of dynamic perforasomes had no effect on flap survival, even based on a nondominant perforator. And the pedicle position affected flap survival.